An Information System Model in Healthcare Supply Chain and Logistics in Thailand - Artaphon Chansamu (International Journal of Supply Chain Management, 2022)
The research about an information system model in healthcare supply chain and logistics in Thailand. The research finding has been found that  an information system model in healthcare supply chain and logistics in Thailand comprises four main components, namely, manufacturer, Purchasers, Healthcare provider and consumer. All elements are connected with information technology namely   namely Drug information, manufacturer information. patient information trading information and data storage. .The research aims to develop and assess an information system model in healthcare supply chain and logistics in Thailand. A sample group  are  ten   experts. The data is analyzed by arithmetic means and standardized deviations .The measurement and the evaluation of an information system model are based on Black-Box Testing. The evaluation result an information system model in healthcare supply chain and logistics in Thailand from ten experts was appropriate in a good level and can be appropriately applied in actual work settings.